Joint Associations of Sedentary Time and Intensity-Specific Physical Activity with Cancer Mortality: A Device-Based Cohort Study of 72,458 Uk Adults - De Moraes-Ferrari, G (Human Kinetics Publishers Inc., 2025)
Background: There are no studies examining the prospective joint association of device-based measures of sedentary time and physical activity (PA) with cancer mortality. We examined the joint associations of sedentary time and intensity-specific PA with cancer mortality in 72,458 adults from UK Biobank. Methods: Participants wore an Axivity AX3 accelerometer on their dominant wrist for at least 3 days (with at least 1 weekend day). Cox regression was performed to estimate hazard ratios (HR) and 95% confidence intervals (CIs) for joint associations of sedentary time and intensity-specific PA (light [LPA], moderate [MPA], and vigorous PA [VPA]) with cancer mortality (reference group: high intensity-specific PA and low sedentary time) adjusted for confounders and mutually adjusted for other PA intensities. Results: Associations between sedentary time and cancer mortality were stronger among participants with low PA, irrespective of the intensity. Compared with participants with lower sedentary time (<11 h/d) and high MPA (median of 49 min/d), HR were 1.27 (95% CI, 0.90–1.78) for high sedentary time and high MPA, 1.35 (95% CI, 1.03–1.77) for high sedentary time and medium MPA (49 min/d), and 1.49 (95% CI, 1.15–1.92) for high sedentary time and low MPA (13 min/d). HR for high sedentary time and low light PA (61 min/d) and high sedentary time and low vigorous PA (1 min/d) were 1.25 (95% CI, 1.02–1.59) and 1.57 (95% CI, 1.20–2.06), respectively. Conclusions: Relatively large amounts of LPA and MPA and small amounts of VPA appeared to attenuate the association between sedentary time and cancer mortality. © 2025 Human Kinetics, Inc.